High levels of boron promote anchorage-independent growth of nontumorigenic cells. (November 2020) - Xu, Huadong; Hashimoto, Kazunori; Maeda, Masao; Azimi, Mohammad Daud; Fayaz, Said Hafizullah; Chen, Wei; Hamajima, Nobuyuki; Kato, Masashi
Abstract: WHO has presented a health-based guideline value for boron in drinking water. That fact indicates that a high level of boron is toxic for humans. However, there is no direct evidence of boron-mediated malignant transformation. In this study, human lung epithelial nontumorigenic BEAS-2B cells and tumorigenic A549 cells were used to investigate the tumorigenic toxicity of boron in vitro . Anchorage-independent growth, a hallmark of malignant transformation, was increased by boron at concentrations of 50, 250 and 500 μM in BEAS-2B cells, though the same concentrations of boron had no influence on anchorage-independent growth of A549 cells. Moreover, boron at concentrations of 250 and 500 μM activated the c-SRC/PI3K/AKT pathway of BEAS-2B cells. The results of our in vitro study suggest that exposure to high levels of boron promotes transforming activity of nontumorigenic cells. Graphical abstract: Image 1 Highlights: Discovery of a high level of boron in well drinking water from Kabul, Afghanistan. Promoted anchorage-independent growth of nontumorigenic cells by 50–500 μM boron. Activated c-SRC/PI3K/AKT pathway in nontumorigenic cells by 250 and 500 μM boron. No effect of 50–500 μM boron on anchorage-independent growth of tumorigenic cells. Promoted transforming activity of nontumorigenic cells by high levels of boron in vitro .